The archaeology and geomorphology of northern Asia : selected works - Michael, Henry N. (Anthropology of the North: translations from Russian sources, 1964)
The eighteen articles appearing in this, the fifth, number of Anthropology of the North: Translations from Russian Sources, were mostly published between the years 1957 and 1963. The exceptions are S.I. Rudenko's "The culture of the prehistoric population of Kamchatka," published in 1948, and A.P. Okladnikov's "Paleolithic remains in the Lena river basin," published in 1953. Thirteen of the articles deal with the archaeology and five with the geomorphology of selected areas of northern Asia. Dr. Chester S. Chard of the University of Wisconsin analyzes the contents and meaning of these articles in his Introduction to the book and fruitfully correlates them with other sources which have been made available to the English-reading specialist over the past few years. In the Notes and References attached to each article, editorial reference has sometimes been added about the availability in English translation of a cited article.